Elevated D-dimer is Associated with Anemia, Immune Dysregulation, and Hepatic–Renal Dysfunction in Acute Burn Patients - Paramita, Anindya; Hariani, Lynda; Zarasade, Lobredia; Syakdiyah, Noer Halimatus; Dewi, Nurrani Mustika; Sandra, Ferry (The Indonesian Biomedical Journal, 2026)
BACKGROUND: Burn injury induced increased risk of venous thromboembolism (VTE) due to hypercoagulability, immobilization, and endothelial injury. Despite this risk, VTE in burn patients often remains clinically undetected. Although D-dimer is widely used as a VTE marker, its utility in burn patients is inconsistent, particularly in the early post-burn period. Therefore, this study was conducted to evaluate the correlation between D-dimer levels and factors related to VTE, including hematologic, coagulation, immunologic, organ function parameters, and burn characteristics.METHODS: An analytical observational study was conducted involving adult patients with acute burn injuries enrolled in Dr. Soetomo General Hospital from March to June 2025. Demographic, anthropometric, burn characteristic, and existing comorbid were documented from subjects’ medical records. Blood samples from subjects were collected immediately via venipuncture. D-dimer was analyzed with Enzyme-Linked Fluorescent Assay (ELFA) method, hematology and coagulation profiles were also assessed using hematology analyzer and automated coagulation system, respectively. Meanwhile, hepatic and renal function were analyzed with chemistry analyzers.RESULTS: Most burn subjects (18 of 20) demonstrated elevated D-dimer levels. Higher D-dimer levels were associated with increased leukocyte counts and upward trend of RDW-CV and RDW-SD. Further analysis among the subjects with elevated D-dimer level showed significant negative correlations were observed between D-dimer levels and anemia-related parameters, including hemoglobin, erythrocyte count, and hematocrit (all p<0.05). Elevated D-dimer was also associated with immune dysregulation, reflected by increased basophil percentages and decreased immunoglobulin (Ig) levels. Additionally, D-dimer levels showed significant positive correlations with aspartate aminotransferase (AST), alanine aminotransferase (ALT), and blood urea nitrogen (BUN), suggesting a link between hypercoagulability and kidney as well as renal dysfunction following burn injury.CONCLUSION: Leukocyte count, RDW-CV, and RDW-SD are higher in burn patient with elevated D-dimer levels, suggesting that high D-dimer might be correlated with VTE. Elevated D-dimer in burn patients correlates with several VTE risks including anemia, immune dysregulation, and hepatic–renal dysfunction, indicating early coagulation activation and systemic injury following burn injury. KEYWORDS: burn injury, D-dimer, hypercoagulability, VTE, anemia, immune dysregulation, organ dysregulation